Estimating the price and production risks of poultry farms in Tartous Governorate - نيوف, أريج (Submission and Review of Research -Biological Sciences Series, 2025)
The research aimed to estimate the price and production risks of broiler farms in Tartous Governorate and to study the relationship between these risks and poultry productivity. The research adopted a descriptive analytical approach to characterize and analyze production and price data during the period (2011-2023) using frequency tables and percentages. Statistical analysis methods were also applied to measure price and production risks. The research results showed an increase in the number of licensed poultry farms, while broiler meat production recorded significant fluctuations, peaking in 2020 and then declining sharply in 2022. It was also found that price risks were high, reaching 6.04 million Syrian pounds. Production risks also showed significant fluctuations in production, reaching 9,405.70 tons. Regarding hypothesis testing, the results showed a statistically significant inverse relationship between price risks and production quantities at a significance level of 0.05, confirming the impact of price fluctuations on production. Meanwhile, the relationship between production risks and production quantities was not statistically significant, reflecting the influence of other factors, such as economic conditions or climate change. It was recommended to provide administrative and financial incentives for formally registering poultry farms, periodically assess production and price risks through a specialized committee with emergency funds and insurance, and train farmers in the use of modern technologies.